The role of organizational support in promoting work-life balance among academic staff: Evidence from Malaysian public universities - Mohamed, Shahrulanuar; Ismail, Erwan; Kudus, Norliah; Abu Hassan, Mahadi; Ab Rahman, Zaizul (Human Resource Management Academic Research Society, 2026)
This study investigates the role of organizational support in promoting work-life balance among academic staff in Malaysian public universities. Work-life balance is a growing concern in higher education institutions due to the increasing demands of teaching, research, and administrative responsibilities that affect the mental health and overall well-being of academics. Despite various organizational initiatives introduced to support employees, the effectiveness of such support remains underexplored in the local academic context. A quantitative survey was conducted involving 300 academic staff from different public universities. The questionnaire examined respondents’ demographic backgrounds, their perceptions of organizational support, and the effectiveness of policies and programs related to work-life balance. The findings reveal that while the majority of respondents (over 65%) perceive moderate to high organizational support in managing work and life responsibilities, satisfaction levels with the actual implementation of these policies remain relatively lower. Key areas of concern include the lack of managerial support, limited involvement of family in organizational programs, and insufficient improvements in work-life initiatives. Although 67% of respondents acknowledged the benefits of existing programs, only 53.7% expressed satisfaction with them. Additionally, many participants agreed that work-life policies should be enhanced and more inclusive, particularly in recognizing family values and individual employee needs. This study highlights the need for stronger organizational commitment and leadership in supporting work-life initiatives, with emphasis on continuous policy improvement, family-inclusive programs, and psychological support systems. The findings contribute to understanding the organizational dynamics that influence academic well-being and offer practical recommendations to promote a healthier and more productive academic workforce in Malaysian public universities.